DISMANTLING INTERCULTURAL COMPETENCE – A PROPOSAL FOR INTERPRETING THE CONCEPT OF CRITICAL CULTURAL AWARENESS IN AN L2 TEACHING CONTEXT - Cierpisz, Agata (Neofilolog, 2019)
The marginal role of intercultural competences in L2 teaching in the Polish context has recently been observed (e.g., Sobkowiak, 2015, Róg, 2016). Too general and often confusing definitions of the fundamental concepts underlying intercultural competence might be one of the rea-sons why L2 teachers reluctantly approach the idea of implementing the intercultural component into their teaching repertoires. The paper aims at discussing the importance of raising students’ critical cultural aware-ness, a central component of Byram’s (1997) model of intercultural com-petence, interpreting and extending its definition using 16 indicators or-ganised into five categories: cultural identity, decentring, reflectiveness and meta-awareness, cultural understanding, and attitudes. The paper ends with three examples of reflective tasks, based on the indicators pre-sented, which can be easily incorporated into L2 teachers’ lesson plans.